Evaluation of the Usability of the SIMRS Application in the Registration Department at Raden Mattaher Jambi Hospital - Billa, Diah Salsa; Yunengsih, Yuyun (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The use of the SIMRS application is necessary because it is related to information management. A good information system results in good information. Nevertheless, from a practical standpoint, medical recorders who serve as outpatient registration officers have challenges while attempting to use the SIMRS application. The level of enjoyment that medical recorders have as users of the SIMRS application is impacted because of these challenges. Therefore, it is very important to conduct usability testing procedures to assess the extent to which the SIMRS application is user friendly. This study's objectives are to measure the usability of the SIMRS application and identify any issues with it by evaluating three usability factors: effectiveness, efficiency, and errors. The researchers employed a combination of research methods for this investigation. Because of this study, six issues were discovered throughout the usability testing process. The findings of the measurement of usability aspects were as follows: 87% for effectiveness aspects, 0.0005 goals per second for efficiency aspects, and 13% for error aspects. The need for adding barcodes for new patient identity data, recommended SIMRS application to do Bridging System and the need for adding fingerprint features to the SIMRS application